Updated estimation of the impact of a Japanese encephalitis immunization program with live, attenuated SA 14-14-2 vaccine in Nepal. - Shyam Raj Upreti; Nicole P Lindsey; Rajendra Bohara; Ganga Ram Choudhary; Sushil Shakya; Mukunda Gautam; Jagat Narain Giri; Marc Fischer; Susan L Hills (Public Library of Science (PLoS), 2017)
Japanese encephalitis (JE) is a mosquito-borne disease that is associated with considerable morbidity and mortality in many Asian countries. The objective of this study was to describe the impact of the JE immunization program using SA 14-14-2 JE vaccine implemented in Nepal during 2006 through 2011. A previous assessment after the initial program implementation phase described a significantly lower post-campaign JE incidence compared to expected incidence; however, the previous evaluation had limited post-campaign data for some districts.JE and acute encephalitis syndrome (AES) data gathered through Nepal's routine surveillance system from 2004 through 2014 were analyzed to assess the impact of the JE immunization program implemented in 31 districts. Expected incidence rates were determined by calculating the incidence of cases per 100,000 person-years in each district before the vaccination campaigns. This rate was applied to the relevant population after the vaccination campaigns, which provided the expected number of cases had the campaign not occurred. The observed incidence rate was the number of reported cases per 100,000 person-years post-campaign. Expected and observed JE and AES cases and incidence rates were compared. The post-campaign JE incidence rate of 0.7 cases per 100,000 was 78% (95% CI 76%-79%) lower than expected had no campaign occurred and an estimated 3,011 (95% CI 2,941-3,057) JE cases were prevented. The post-vaccination AES incidence of 5.5 cases per 100,000 was 59% (58%-60%) lower than the expected and an estimated 9,497 (95% CI 9,268-9,584) AES cases were prevented.This analysis strengthens previous findings of the substantial impact of Nepal's JE immunization program using SA 14-14-2 JE vaccine.